Th9 Cell Differentiation and Its Dual Effects in Tumor Development - Chen, Tao; Guo, Jufeng; Cai, Zhenhai; Li, Binghao; Sun, Lingling; Shen, Yingying; Wang, Shengdong; Wang, Zhan; Wang, Zenan; Wang, Yucheng; Zhou, Hao; Cai, Zhijian; et al. (Frontiers in Immunology, 2020)
With the improved understanding of the molecular pathogenesis and characteristics of cancers, the critical role of the immune system in preventing tumor development has been widely accepted. The understanding of the relationship between the immune system and cancer progression is constantly evolving, from the cancer immunosurveillance hypothesis to immunoediting theory and the delicate balance in the tumor microenvironment. Currently, immunotherapy is regarded as a promising strategy againstcancers. Although adoptive cell therapy (ACT) has shown some exciting results regarding the rejection of tumors, the effect is not always satisfactory. Cellular therapy with CD4+ T cells remains to be further explored since the current ACT is mainly focused on CD8+ cytotoxic T lymphocytes (CTLs). Recently, Th9 cells, a subgroup of CD4+ T helper cells characterized by the secretion of IL-9 and IL-10, have been reported to be effective in the elimination of solid tumors and to exhibit superior antitumor properties to Th1 and Th17 cells. In this review, we summarize the most recent advances in the understanding of Th9 cell differentiation and the dual role, both anti-tumor and pro-tumor effects, of Th9 cells in tumor progression.